2000
DOI: 10.2307/1423364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress Induced by a Simulated Shooting on Recall by Police and Citizen Witnesses

Abstract: Two experiments address the accuracy of citizen and police witnesses in recalling stressful events. Participants saw 2 training scenarios. Experiment 1 evaluated the effects of active engagement and the presence of a simulated shooting on police officers' memory for details. Police officers recalled significantly fewer details from the scenario in which a shooting occurred. Active engagement did not influence recall. Experiment 2 compared the memory performance of police and citizen witnesses. Manipulation che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…There were few differences in recall between officers who took part in a 'shoot' scenario in which they fired their weapon compared to officers in a 'no shoot' scenario who did not open fire. Stanny and Johnson (2000) combined a similar virtual reality simulation with a within-participant manipulation of 'shoot' and 'no shoot' scenarios. They found that police and civilian witnesses, who showed increased physiological activation during the violent 'shoot' scenarios, recalled fewer correct details in comparison to their recall of a less violent 'no shoot' scenarios.…”
mentioning
confidence: 99%
“…There were few differences in recall between officers who took part in a 'shoot' scenario in which they fired their weapon compared to officers in a 'no shoot' scenario who did not open fire. Stanny and Johnson (2000) combined a similar virtual reality simulation with a within-participant manipulation of 'shoot' and 'no shoot' scenarios. They found that police and civilian witnesses, who showed increased physiological activation during the violent 'shoot' scenarios, recalled fewer correct details in comparison to their recall of a less violent 'no shoot' scenarios.…”
mentioning
confidence: 99%
“…The results from past work, however, have provided inconsistent support for this thesis. Specifically, some studies show that arousal decreases the accuracy of eyewitness identifications (Deffenbacher et al, 2004;Stanny & Johnson, 2000), whereas others suggest that arousal may enhance memory performance (Bornstein, Liebel, & Scarberry, 1998).…”
Section: Estimator Variablesmentioning
confidence: 99%
“…For example, police officers recall fewer details from scenarios in which a shooting occurred than those without a shooting (Stanny & Johnson, 2000), and memory for contextual details is worse for emotionally arousing than nonemotional events (Kensinger, Piguet, Krendl, & Corkin, 2005;Schmidt, 2002). Memories for shocking events may import elements from other events, such as television footage seen later (Pezdek, 2003;Neisser & Harsch, 1992), and memory for peripheral details of such events is worst among people who find the event most emotionally powerful (Schmidt, 2004).…”
Section: Introductionmentioning
confidence: 99%